COLLABORATIVE ADAPTIVE SERVICE GOVERNANCE : THEORY INTEGRATED SERVICE GOVERNANCE PUBLIC - Kristanto Setyo Utomo; Hendrik Toda; Melkisedek N B C Neolaka; Maria L Lino (RADJA PUBLIKA, 2026)
The development of increasingly complex and dynamic public problems, marked by limited institutional capacity, demands a governance approach that can explain how public services can remain effective under various conditions. However , the literature about collaborative governance , adaptive governance , institutional capacity , and public service governance Still develop in a way separated so that Not yet available framework theoretical integration​ fourth perspective said . Research This aim develop Collaborative Adaptive Service Governance (CASG) as theory level medium For explain governance mechanisms​ service effective public research​​ use approach Theory Building Systematic Literature Review (TBSLR) of 56 articles indexed by Scopus for the period 2008–2026. Analysis done through stages open coding , axial coding , selective coding , conceptual integration , and theory synthesis . Research result identify four construct main , namely collaborative dynamics , adaptive capability , institutional capacity , and service outcomes , which form mutually beneficial governance mechanisms​ depends . Findings show that effectiveness service public is results interaction dynamic between collaboration , capacity adaptive , and capacity strengthened institutions​ through mechanism bait recursive governance mechanism . Research This conclude that CASG provides framework theoretical bridging integration​ various tradition literature governance as well as expand understanding about connection dynamic between governance and service​ public .